IMPLEMENTASI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DALAM PELAYANAN DESA MELALUI PENGEMBANGAN APLIKASI INDEKS DESA MEMBANGUN DI DESA TAPOS 1 KECAMATAN TENJOLAYA KABUPATEN BOGOR PROVINSI JAWA BARAT - Rumsowek, Sfase Jusde Juan Christian; Khair, Otti Ilham; Setianingsih, Susiana (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2023)
This researcher aims to find out how mature the implementation of an electronic-based government system is in service by using the Village Development Index application in Tapos I Village, Tenjolaya District, Bogor Regency, West Java Province. The research method used was qualitative to understand the abilities that were able to be carried out by the research subjects, while the data collection techniques used observation, interviews and documentation studies. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Then the data validation techniques used were research triangulation, methodological triangulation and theoretical triangulation. The results of the study show that the Implementation of an Electronic-Based Government System (SPBE) in Village Services through the Development of the Village Building Index Application. What is said is the Development Village Index (IDM) by showing the level of independence of the village with the IDM application by looking at the human and economic resources of the community as well as network constraints that are not strong so that the input of IDM data is hampered, the application is still constrained when the data transmission process is interrupted by the program itself, this happens when the server, especially the Village Development Index application, not only 1 village uses the IDM application but all villages in Indonesia. Tapos I Village is still classified as a developed village with an IDM score of 0.7614. For this reason, the Tapos I Village government seeks to increase the potential of its human resources and improve the community's economy in the field of food security and fisheries.